The Presence of the Withdrawn: Review of Representing the Modern Animal in Culture, ed. Jeanne Dubino, Ziba Rashidian, and Andrew Smyth (2014) - Hutchison, Bill (Humanimalia, 2017)
Jeanne Dubino, Ziba Rashidian, and Andrew Smyth, eds., Representing the Modern Animal in Culture. New York: Palgrave Macmillan, 2014. 266 pp. $95.00 hb.